2012
DOI: 10.1007/s00265-012-1356-x
|View full text |Cite
|
Sign up to set email alerts
|

Social competition masculinizes the communication signals of female electric fish

Abstract: Male intrasexual competition and female choice explain the evolution of male ornaments. Except in sex-rolereversed taxa, female ornaments have been regarded as an epiphenomenon of genetic correlation, with no femalespecific function or independently selected basis. Females from species with conventional sex roles may still experience some degree of female-female competition and male choice that could explain the persistence of female ornaments. We studied the effect of female competition on the expression of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Signal plasticity among females was shown to save energy during the day (Salazar and Stoddard, 2008;Stoddard et al, 2007) but social consequences of female signal plasticity were not understood. Recently, we have found that female signals also respond to changes in the social environment in ways similar to males (Gavassa et al, 2012a). Both in field observations and laboratory manipulations, females increase the amplitude of the EOD in response to increases in population density, while the duration of the EOD's second phase increases in response to a greater ratio of females to males.…”
Section: Is Female Eod Plasticity Functionally Similar To That Of Males?mentioning
confidence: 99%
See 2 more Smart Citations
“…Signal plasticity among females was shown to save energy during the day (Salazar and Stoddard, 2008;Stoddard et al, 2007) but social consequences of female signal plasticity were not understood. Recently, we have found that female signals also respond to changes in the social environment in ways similar to males (Gavassa et al, 2012a). Both in field observations and laboratory manipulations, females increase the amplitude of the EOD in response to increases in population density, while the duration of the EOD's second phase increases in response to a greater ratio of females to males.…”
Section: Is Female Eod Plasticity Functionally Similar To That Of Males?mentioning
confidence: 99%
“…Females in the field increase EOD second phase duration and androgen levels in proportion to intrasexual competition (Table2) (Gavassa et al, 2012a). However, in the laboratory, female intrasexual competition increases EOD second phase duration without detectable changes in androgen levels (Gavassa et al, 2012a), although experimental increase of androgen levels reliably and consistently increases EOD duration in both sexes (Allee et al, 2009;Gavassa et al, 2011;Goldina et al, 2011;Pouso et al, 2010;Silva et al, 2002).…”
Section: Is Female Eod Plasticity Functionally Similar To That Of Males?mentioning
confidence: 99%
See 1 more Smart Citation
“…Reproductive seasonality, life history, and ecology in B. gauderio are documented by several authors (Gavassa et al, 2012;Giora et al, 2014;Miranda et al, 2008;Quintana et al, 2004;Silva et al, 2003). It breeds during the austral summer, with maturation probably triggered by rising temperature and a change in photoperiod.…”
Section: Population Variationmentioning
confidence: 99%
“…It breeds during the austral summer, with maturation probably triggered by rising temperature and a change in photoperiod. During the breeding season it lives in dense social groups, and exhibits a sex ratio of mature individuals highly skewed towards females (around 3:1, despite observations of a primary sex ratio close to unity in a long-term laboratory population), possibly due to elevated male mortality related to stress from intrasexual competition (Gavassa et al, 2012;Miranda et al, 2008). Males exhibit a wider spacing, and move less than females -consistent with a polygynous or polygynandrous mating strategy resembling exploded lek polygyny .…”
Section: Population Variationmentioning
confidence: 99%